Development of a Special Tool for Prefilter Glass Removal on Excavator PC400-8 - Hendro Purwono (Talenta Publisher, 2025)
Periodic maintenance of hydraulic excavators, such as the PC400-8, is essential to ensure optimal performance in tasks like loading materials such as soil, rocks, and others into dump trucks. One of the challenges during periodic maintenance is the removal of the prefilter glass, which is often difficult due to the hardness of the material. The tool currently used, a standard filter wrench, lacks precision and frequently slips, increasing the risk of breaking the prefilter glass and causing potential injury to mechanics. To address this issue, this study develops an innovative prefilter glass removal tool using the 7 Ups++ method, an approach that involves evaluating aspects such as usability, efficiency, ergonomics, safety, sustainability, precision, and quality. The innovation aims to reduce the risk of glass breakage and enhance the safety of mechanics. The research results indicate that the designed tool can significantly reduce difficulties and is estimated to reduce the risk of prefilter glass breakage by approximately 90% during use, while also saving 50–105 seconds per operation. This leads to a performance improvement of 83%–87.5% and enhanced occupational safety, and has the potential to make a positive contribution to periodic service procedures and workplace safety in the heavy equipment industry.